Educação ambiental não-formal : a práxis coletiva dos pescadores artesanais no rio Paraguai Cáceres/Mato Grosso/Brasil - Bezerra, Darci Ordonio dos Santos (Universidade Federal de São Carlos, 2009)
Cáceres is situated to the left edge of High Paraguai river, in the Region Center-West, Brazil, possessing co-ordinated: south latitude (16º 11' 42' ') e longitude west (57º 40' 51' ') with altitude of 118 meters above sea level. This research was carried through with the objective to know the perception of the professional fishing of the Z-2 Colony with regard to the ambient functions, potentialities and to the impacts of the Paraguay river throughout the urban perimeter of the city of Cáceres/MT, in order to become possible the participation of all the involved ones in activities of Environmental Education, aiming at the environment conservation and the improvement of quality of life in the daily one of these people. Fishing has great importance for the Cáceres population, therefore it is the economic base for many families of low income who use waters of High Paraguai river, vestibule of the Pantanal Weed. The used methodological procedures for the collection of data had been documentary analysis, participant comment, informal dialogues, interviews, works of field, application of questionnaires, accomplishment of workshops, dynamic of group, lectures, systematization and interpretation of data. As results, we concluded that the professional fishing have faced a series of problems generated for fish predatory, for the deforestation and the tourism not guided, inconsequence practical that come causing difficulties in the supply fishing boat (amount) and in the biodiversity of ictiofauna (species) throughout the time, beyond social environmental impacts in the Paraguai river, as exclusion of the professionals of fishes, sanding up and erosion of the edges. Many of them point the polluting activities and predatory, they are conscientious that they can help the environment agencies and present suggestions for the questions of professional and sportive´s fishes. From the identification of the collective problems that face and the interpretation of the perception that they possess on such questions, it was possible to carry through practical of Environmental Education, taking in consideration the open and critical dialogue. It was evidenced that the environment management of Cáceres applied to the Paraguai river is not adjusted, lacking a rigorous fiscalization for it fishes predatory and bigger opening for the participation of the professional fishing in the public administration.
Keywords: Ecologia humana; Educação e percepção ambiental; Paraguai, Rio (MT); Pantanal mato-grossense; Pescadores artesanais; Perception and environmental education; Paraguai river; Pantanal; Professional fishing; Ecologia humana; Educação e percepção ambiental; Paraguai, Rio (MT); Pantanal mato-grossense; Pescadores artesanais; Perception and environmental education; Paraguai river; Pantanal; Professional fishing; CIENCIAS BIOLOGICAS::ECOLOGIA